Analisis Penerapan Terminal Booking System (TBS) Terhadap Kelancaran Arus Barang di Pelabuhan Utama Tanjung Priok - Jasmine, Shifa El; Sihaloho, Otri Wani; Ratnaningsih, Dyah; Amrullah, Romanda Annas (Universitas Pahlawan Tuanku Tambusai, 2025)
Tanjung Priok Port is one of the main ports in Indonesia that plays an important role in supporting national and international goods flows. As a main port, it will certainly faces challenges in managing the flow of goods due to the high volume of activities which often triggers congestion and long waiting times. This study aims to analyze the effect of implementation Terminal Booking System (TBS) on the smooth flow of goods at the port. Using a descriptive quantitave method, data were collected through surveys of respondents involved in port operations. The collected data were analyzed using statistical techniques with SPSS version 27 to measure the effect of TBS on time efficiency an the smoothness of loading and unloading processes. The results show that the implementation of TBS has a positive and significant impact on reducing waiting times, improving logistics efficiency, and enhancing coordination among the various stakeholders involved. This research supports the sustainable development of TBS as well as system system integration to promote the digitalization of port operations. Keyword: Cargo flow, Digitalization Loading and unloading, Quantitative, TBS